EFFECT OF ARTESIAN WATER WITH A GAS NANOBUBBLES (Ar, O2, N2, CO2, AIR) ON BIOCHEMICAL PROCESSES IN SPRING WHEAT SEEDS - O. M, Kanunnikova; A.V, Lednev; V.VАksenova; A.V, Lozhkin; V. I, Kozhevnikov; A.V., Trubachev (IJRDO-Journal of Applied Science, 2017)
The influence of artesian water with nanobubbles of different gases (Ar, O2, N2, CO2, air) on the intensity of metabolic processes in seeds of spring wheat. The effect of pre-soaking the seeds and spraying of seedlings on yield of wheat was investigated in a field experiment. It was found that the degree of swelling of seeds in the source of artesian water and water with nanobubbles was the same, but the kinetics of germination varied considerably. Metabolic processes in the seeds are accelerated in the presence of gas nanobubbles in water. The observed effect was similar to a temperature increase of several degrees. The most intensive metabolic processes occur in seeds in water with Ar and CO2 nanobubbles. Soaking of the wheat seed by water with gas nanobubbles have contributed to a statistically significant increase in wheat yields. The greatest influence on this indicator was provided by the water with argon nanobubbles. Argon has no effect on metabolic processes in seeds and plants. The effect of water with argon nanobubbles can be explained only by the presence of the electrical double layer, which has redox properties and affects metabolic processes at different stages of wheat growth.